2020
DOI: 10.3389/fcell.2020.534268
|View full text |Cite
|
Sign up to set email alerts
|

Advances in CMV Management: A Single Center Real-Life Experience

Abstract: CMV infection is a major challenge in allogeneic stem cell transplantation (allo-SCT). The changing landscape in CMV management includes the introduction of letermovir in prophylaxis of high-risk patients and the source of CMV DNA monitoring (plasma-PL vs. whole blood-WB), for pre-emptive therapy (PET) initiation. We report here how our real-life experience in CMV management evolved, following letermovir registration. We focus on: (i) the effects of systematic use of letermovir for CMV prophylaxis in high-risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…This observation is of interest and may be related to the intensification of fungal prophylaxis in high-risk patients according to the BATMO protocol, with posaconazole instead of fluconazole (Table 1), in accordance with the risk score proposed by Stanzani et al (13). Finally, focusing on viral infections, the impact of CMV reactivations by day +100 (any level of DNA) significantly reduced moving from Cohort A to Cohort B (51% in Cohort A vs. 15% in Cohort B; p=0.00001; Supplementary Figure S4B), and this is in line with our recently published study (26). This reflects the efficacy of letermovir prophylaxis, but the issue of CMV is not completely resolved, as the OS of patients with a CMV reactivation is significantly impaired in comparison to those without this event (Supplementary Figure 4B).…”
Section: Discussionsupporting
confidence: 90%
“…This observation is of interest and may be related to the intensification of fungal prophylaxis in high-risk patients according to the BATMO protocol, with posaconazole instead of fluconazole (Table 1), in accordance with the risk score proposed by Stanzani et al (13). Finally, focusing on viral infections, the impact of CMV reactivations by day +100 (any level of DNA) significantly reduced moving from Cohort A to Cohort B (51% in Cohort A vs. 15% in Cohort B; p=0.00001; Supplementary Figure S4B), and this is in line with our recently published study (26). This reflects the efficacy of letermovir prophylaxis, but the issue of CMV is not completely resolved, as the OS of patients with a CMV reactivation is significantly impaired in comparison to those without this event (Supplementary Figure 4B).…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, several factors may have slowed down this policy such as the variable time interval for the authorization of letermovir prescription at different European countries, the costs of the drug prophylaxis and the need for every allogeneic-HCT unit to reformulate the annual budget and approve the costs for letermovir, and the attitude of the centres and hematologists to utilise in the routine practice the indications coming from a clinical trial. Retrospective data from "real world" use and cost-effectiveness model analysis, con rmed that anti-CMV primary prophylaxis with letermovir is associated with a reduction of CMV infections, shorter hospitalizations, reduced costs and improvement of hematological and renal parameters [21][22][23] . In this regard, our interpretation of existing data support that a broader use of letermovir primary prophylaxis in the next future may result into an improvement of the overall transplant outcomes, as suggested by a post-hoc analysis on overall mortality conducted on the patient recruited in the phase III trial of letermovir versus placebo 24 .…”
Section: Discussionmentioning
confidence: 97%
“…Other real-world experiences have also been published. An Italian study compared 45 patients undergoing prophylaxis with LET with a retrospective cohort that did not receive prophylaxis ( 38 ). Results showed that prophylaxis was highly effective and safe in reducing the incidence of CSCI when administered from day 0 to day +100.…”
Section: Discussionmentioning
confidence: 99%